Towards the Oral Treatment of Ileo-Colonic Inflammatory Bowel Disease with Infliximab Tablets: Development and Validation of the Production Process - Bahez Gareb; Silke Posthumus; Max Beugeling; Pauline Koopmans; Daan J. Touw; Gerard Dijkstra; Jos G.W. Kosterink; Henderik W. Frijlink (MDPI AG, 2019)
Infliximab (IFX) is an intravenously administered monoclonal antibody antagonizing the effects of tumor necrosis factor-alpha (TNF) systemically and is efficacious in the treatment of inflammatory bowel disease (IBD). However, studies suggest that the anti-inflammatory effects result from local immunomodulation in the inflamed regions. Furthermore, topical inhibition of TNF in IBD ameliorates inflammation. We therefore hypothesized that orally administered IFX targeted to the ileo-colonic region in IBD may be an efficacious new treatment option. This study describes the development and validation of the production process of ileo-colonic-targeted 5 mg IFX tablets (ColoPulse-IFX) intended for the oral treatment of IBD by means of producing three consecutive validation batches (VAL1, VAL2, and VAL3, respectively). UV-VIS spectroscopy, HPLC-SEC analysis (content, fragments, aggregates), fluorescence spectroscopy (tertiary protein structure), and ELISA (potency) showed no noticeable deviations of IFX compounded to ColoPulse-IFX compared to fresh IFX stock. The average ± SD (n = 10) IFX content of VAL1, VAL2, and VAL3 was 96 ± 2%, 97 ± 3%, and 96 ± 2%, respectively, and complied with the European Pharmacopeia (Ph. Eur.) requirements for Content Uniformity. The average ± SD (n = 3) ColoPulse-IFX potency was 105 ± 4%, 96 ± 4%, and 97 ± 5%, respectively, compared to fresh IFX stock. The IFX release profile from the tablet core was complete (≥85%) after 10 min in simulated ileum medium. The in vitro coating performance of ColoPulse-IFX showed that the formulation was targeted to the simulated ileo-colonic region. Stability data showed that ColoPulse-IFX was stable for up to 6 months stored at 25 °C/60% RH. Based on these results, the production process can be considered validated and its application is discussed in light of the rationale and available evidence for the topical treatment of IBD with IFX.